How do Australian adult mental health clinicians manage the challenges of working with parental mental illness? A phenomenological study. Issue 3 (7th December 2017) - Tchernegovski, Phillip; Reupert, Andrea E.; Maybery, Darryl J.
Abstract: Adult mental health clinicians face a range of challenges that hinder their use of family‐focused practices when working with consumers who are parents. The purpose of this study was (a) to examine clinicians' experiences when working with parents and (b) identify strategies they found to be effective when working with parents. Eleven Australian mental health clinicians were recruited who regularly worked with consumers who are parents. Semistructured interviews were conducted within a qualitative paradigm and analysed using interpretative phenomenological analysis. Themes were identified which related to (a) managing sensitive parenting conversations, (b) making decisions about child safety in unclear or unpredictable situations, and (c) working with child protection services. Participants had developed strategies for managing the challenges of the first two practice issues and suggested organizational changes that could facilitate collaboration with child protection services. The findings highlight that the challenges of working with parents with mental health issues cannot be addressed with a one‐size‐fits‐all approach. Initiatives to facilitate the effective support of parents and their children need to be informed by contextual factors, including clinical practice.